The Contribution of Social Movement Theory to Understanding Genocide: Evidence from Rwanda. Issue 2 (1st December 2019) - Luft, Aliza
Abstract : Recent years have witnessed a turn in the field of contentious politics toward the study of political violence, yet scholars have yet to focus their lens on genocide. Moreover, research on genocide is characterized by fundamental disagreements about its definition, origins, and dynamics, leading to a lack of generalizable theory. As a remedy, this article suggests that research on genocide can be improved by incorporating concepts from social movements. After reviewing the history of research on social movements and genocide, I analyze civilian participation in the Rwandan genocide as an example of how social movement theory helps explain civilian mobilization for genocide. Finally, I propose that a contentious politics approach to genocide would consider it one among many forms of contentious collective action, analyzable within the existing framework of social movement theory.